2012
DOI: 10.1007/s00213-012-2961-0
|View full text |Cite|
|
Sign up to set email alerts
|

Somatostatin antagonist induces catalepsy in the aged rat

Abstract: The combination of aging and brain somatostatin deficiency can lead to catalepsy in rats. Since both factors are frequently observed in PD patients, the present results might be of relevance for pathogenesis of extrapyramidal signs in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
7
16
0
Order By: Relevance
“…As shown there, cycloSOM initiates cataleptic response at the dose of 10 µg, while smaller doses are inactive (8). Similar results were obtained in the present work, wherein cycloSOM at the doses of 0.2 -5.0 µg had no effects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As shown there, cycloSOM initiates cataleptic response at the dose of 10 µg, while smaller doses are inactive (8). Similar results were obtained in the present work, wherein cycloSOM at the doses of 0.2 -5.0 µg had no effects.…”
Section: Discussionsupporting
confidence: 92%
“…CycloSOM at the doses of 0.2, 1.0, 5.0, and 10.0 µg and histamine at the doses of 1.0 and 10.0 µg were administered intracerebroventricularly (i.c.v.). The doses were selected according to the previous studies (8,13).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that HAL increased the duration of cataleptic episodes, an often used marker of APD side-effects (Ionov et al, 2013), in a dose-dependent manner in both young and aged mice. However, the severity of cataleptic episodes is increased in aged mice, consistent with previous reports (Barnes et al 1990; Campbell et al 1988; Wiley and Evans 2008).…”
Section: Discussionmentioning
confidence: 74%
“…One of the iPD-associated brain abnormalities is a fall in somatostatin levels (for refs., see [8,9]). These changes may be of pathogenic importance as somatostatin can stimulate dopaminergic neurotransmission [10][11][12].…”
Section: Introductionmentioning
confidence: 98%